2013
DOI: 10.1111/hae.12248
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of MR imaging as a tool for evaluating haemophilic arthropathy in children

Abstract: Summary Our purposes were to determine: (i) whether there is direct evidence that currently available MRI techniques are accurate for early diagnosis of pathological findings in haemophilic arthropathy; (ii) whether there is an MRI scoring system that best correlates with clinical/radiological constructs for evaluation of haemophilic arthropathy; (iii) whether there is an MRI scoring system that best correlates with clinical/radiological constructs for evaluation of haemophilic arthropathy. Articles were scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 47 publications
0
36
0
Order By: Relevance
“…In the last 15 years, several MR‐based scoring systems have been proposed . MRI can depict both soft tissue and osteochondral changes in reproducible and measurable ways that allow proper follow‐up, and is considered the reference standard imaging technique for assessment of haemophilic arthropathy . First‐generation scores include the Denver and the European score.…”
Section: Scoring Of Haemophilic Arthropathymentioning
confidence: 99%
See 1 more Smart Citation
“…In the last 15 years, several MR‐based scoring systems have been proposed . MRI can depict both soft tissue and osteochondral changes in reproducible and measurable ways that allow proper follow‐up, and is considered the reference standard imaging technique for assessment of haemophilic arthropathy . First‐generation scores include the Denver and the European score.…”
Section: Scoring Of Haemophilic Arthropathymentioning
confidence: 99%
“…Previous investigation has shown that the use of gadolinium contrast agent is not useful for evaluating chronic haemophilic arthropathy due to the obscuration of synovial enhancement by adjacent haemosiderin deposition in cases of massive haemosiderin impregnation within the synovium . In unenhanced MR studies, the low‐to‐intermediate T1 signal hypertrophied synovium cannot be separately discriminated from low T1 signal joint effusion or low T1, T2 or GRE signal intra‐articular haemosiderin . This usually results in underestimation of the degree of synovial hypertrophy on MRI.…”
Section: Limitations Of Mri and Sources For Pitfallsmentioning
confidence: 99%
“…Magnetic Resonance Imaging (MRI) is the most sensitive imaging modality to demonstrate early intra-articular joint changes. 8 As MRI is relatively expensive and time consuming, routine assessment of multiple joints of haemophilia patients is not feasible. As ultrasound showed to be highly accurate in assessing synovial hypertrophy, it may provide an alternative for MRI.…”
mentioning
confidence: 99%
“…Haemophilia Early Arthropathy Detection with UltraSound), ali z MR slikanjem po protokolu IPSG (angl. International Prophylaxis Study Group) (90,91).…”
Section: Vrste Preventivnega Zdravljenjamentioning
confidence: 99%